Pengaruh Penambahan Dosis Pupuk Fosfat terhadap Pertumbuhan dan Hasil Tanaman Jagung (Zea Mays, L) pada Inceptisol asal Jatinangor - eso solihin; Rija Sudirja; Apong Sandrawati; Maya Damayani; Nadia N. Kamaluddin (Soilrens, 2019)
Corn is one of the important commodities in Indonesia that is not only used as food but also as livestock feed and industry, as well as alternative fuels (biofuels). Degradation of soil fertility became one of the factors limiting the production of this commodity. The purpose of this study was to determine the effect of innovative phosphate fertilizer on the growth and yield of sweet corn on Inceptisols with low fertility. The research was conducted from September 2018 to January 2019. Randomized Block Design (RBD) was used with treatment arrangements as follows: A = Control (without P), B = Recommended NPK dosage (300 kg / ha urea + 150 kg / ha SP-36 + 50 kg / ha K), C = ¼ P (300 kg / ha N + 25 kg / ha SP-36 Inv + 50 kg / ha K), D = 1/2 P (300 kg / ha N + 50 kg / ha SP36 Inv + 50 kg / ha K), E = ¾ P (300 kg / ha N + 75 kg / ha SP-36 Inv + 50 kg / ha K), F = 1 P (300 kg / ha N + 100 kg / ha SP-36 Inv + 50 kg / ha K), G = 1 ¼ P (300 kg / ha N + 125 kg / ha SP-36 Inv + 50 kg / ha K), H = 1½ P (300 kg / ha N + 50 kg / ha SP-36 Inv + 150 kg / ha K), I = 1 ¾ P (300 kg / ha N + 175 kg / ha SP-36 Inv + 50 kg / ha K), J = 0 (Without NPK). The results showed that the SP-36 innovative inorganic fertilizer that was given together with urea and KCl increased the yield of sweet corn equivalent to the standard yield of corn in NPK fertilizer. The treatment with the highest results is 1½ P doses of SP-36 innovation results and P from standard NPK both of which are equivalent to 150 kg / ha P. The yield of sweet corn yields ranges from 21.16 - 21.56 tons per hectare.